Adaptability and Flexibility of the Human Motor System: Implications for Neurological Rehabilitation. Issue 1 (2001) - Mulder, Theo; Hochstenbach, Jacqueline
Abstract : This article stresses the plasticity of the adult sensorimotor cortex in response to various injuries or environmental changes. The dominant role of sensory input is discussed. A number of studies are presented that show how input may lead to learning and change. Learning is discussed in relation to recovery. It is shown how concepts from the field of motor control and learning may be used for improving neurological rehabilitation. Specific attention is given to the variability of input, the meaningfulness of input, and the role of the learning context. The learning context and the application context should have essential characteristics in common, otherwise transfer of learning will be non-optimal. It is argued that learning landscapes are necessary in order to treat patients in such a way that he learned skills are transferable to situations outside the hospital.